Comparison of Quadratus Lumborum Block and Rectus Sheath Block for Postoperative Analgesia in Single-Port Laparoscopic Adnexal Surgery: A Randomized Controlled Trial - Dongju Kim; Seunguk Bang; Jihyun Chung; Youngin Lee; Hyun-Jung Shin; Yoonji Park (Medicina, 2025)
Background and Objectives: Regional anesthesia is a key component of multimodal analgesia following minimally invasive gynecologic surgery. However, single-port laparoscopic adnexal surgery differs anatomically and physiologically from multiport or open approaches, particularly in terms of incision site, tissue handling, and pain characteristics. Despite its increasing use, evidence supporting procedure-specific regional analgesic protocols for this approach remains limited. This study aimed to compare the analgesic efficacy of quadratus lumborum block (QLB) and rectus sheath block (RSB) in this surgical context. Materials and Methods: In this randomized controlled trial, 68 patients undergoing single-port laparoscopic adnexal surgery were randomly assigned to receive either QLB or RSB at the end of surgery. Four patients were excluded due to missing patient-controlled analgesia (PCA) data, resulting in 64 patients analyzed (QLB group: n = 32; RSB group: n = 32). The primary outcome was cumulative opioid consumption over the first 24 postoperative hours. Secondary outcomes included interval-based opioid consumption, time to first PCA bolus, postoperative pain scores, and incidence of postoperative nausea and vomiting (PONV). Results: The RSB group demonstrated significantly lower cumulative opioid consumption at 24 h postoperatively (132.9 [61.3, 338.4] µg vs. 453.0 [253.1, 811.0] µg, p < 0.001). This trend persisted across most postoperative time points up to 48 h. Interval-based opioid consumption was also lower in the RSB group during 0–24 h and 32–48 h intervals (each comparison p < 0.05). The time to first PCA bolus was significantly longer in the RSB group (56.5 [41.0, 340.3] minutes vs. 40.5 [33.3, 68.8] minutes; p = 0.014), and Kaplan–Meier analysis confirmed a delayed first bolus request in the RSB group (log-rank p = 0.007). Pain scores and postoperative nausea and vomiting incidence were comparable between groups. Conclusions: Compared with QLB, RSB provided similar pain relief with significantly lower opioid consumption following single-port laparoscopic adnexal surgery. These findings highlight the potential advantages of RSB in enhancing analgesic efficiency and support the development of procedure-specific regional analgesia protocols tailored to this surgical approach.